2014
DOI: 10.1063/1.4871991
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet digital image correlation (UV-DIC) for high temperature applications

Abstract: A method is presented for extending two-dimensional digital image correlation (DIC) to a higher range of temperatures by using ultraviolet (UV) lights and UV optics to minimize the light emitted by specimens at those temperatures. The method, which we refer to as UV-DIC, is compared against DIC using unfiltered white light and DIC using filtered blue light which in the past have been used for high temperature applications. It is shown that at low temperatures for which sample glowing is not an issue all three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…Therefore, the boundary between the speckle pattern and the material surface must remain intact during deformation. (16) Solutions with bare material surfaces (9,17,18) have been proposed to overcome this issue instead of applying a coating (19) or using paint deposition. (20) By using the natural local features produced from bare material surfaces, the displacement can be directly calculated from the surface features without special surface preparation.…”
Section: Speckle Pattern For Dic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the boundary between the speckle pattern and the material surface must remain intact during deformation. (16) Solutions with bare material surfaces (9,17,18) have been proposed to overcome this issue instead of applying a coating (19) or using paint deposition. (20) By using the natural local features produced from bare material surfaces, the displacement can be directly calculated from the surface features without special surface preparation.…”
Section: Speckle Pattern For Dic Methodsmentioning
confidence: 99%
“…For this purpose, grit-400 sandpaper is used to manually grind the bare material surface, and the variable gray intensity pattern can be generated at the material surface owing to the different levels of optically rough scattering, (21) in contrast to a speckle pattern generated by painting the surface. (9) The change in contrast was used as a random pattern and the speckle pattern acted as the carrier of surface deformation. Additionally, the ground surface of the sample was benefited by the removal of any residual surface damage.…”
Section: Speckle Pattern For Dic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Chen et al and Pan et al applied the blue-filtering technique to stereo-DIC -in which two cameras are used to make three-dimensional (3D) measurements -at temperatures up to 1100 and 1200°C, respectively [3,4]. Most recently, Berke and Lambros showed that the temperature range can be extended even further by using ultraviolet lighting and optics, which operate at an even shorter wavelength than blue light [6].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the increasing interest in applications involving significant thermal effects, such as aero-engines, spacecraft re-entry, aircraft hypersonic flight, and nuclear power applications, recent efforts have extended the upper temperature limit of the DIC technique by the use of optical bandpass filters and narrow band lighting, which reduces the influence of light radiated by the specimen at high temperatures [1][2][3][4][5][6]. Grant et al demonstrated this approach for hightemperature DIC by using blue light along with blue range bandpass filters to measure the coefficient of thermal expansion of RR1000 (a nickel-based alloy) at temperatures up to 1000°C with two-dimensional (2D)-DIC [1].…”
Section: Introductionmentioning
confidence: 99%